Neuropsychiatric Sequalae of Fahr’s Disease: An Atypical Presentation of Psychosis - Lowton, Karishma; Miseer, Prinesh; Talatala, Mvuyiso (British Journal of Healthcare and Medical Research, 2025)
Background: Fahr’s Syndrome is a rare neurodegenerative disorder characterised by bilateral, symmetrical calcifications of the basal ganglia, thalami, hippocampus, cerebral cortex, cerebellum and centrum semiovale. The neurological symptoms include motor symptoms, gait and sensory abnormalities; and seizures. Neuropsychiatric manifestations vary from delirium, depression, psychosis and mania with neurocognitive symptoms follow subcortical dysfunction. Case Report: Ms EC is a 42-year-old female who presented as an index patient following a month of aggressive behaviour, mania and psychosis. She displayed subcortical neurocognitive symptoms for an unknown duration. Her past medical history revealed adult-onset epilepsy four years prior to this presentation with her last reported seizure in 2018. Results: Calcium, magnesium and phosphate were subtherapeutic. EEG displayed abnormal ictal activities and a long bone x-ray indicating hyperostosis. CT brain imaging revealed linear ependymal calcification along occipital horns of the lateral ventricles, bilateral basal ganglia and thalamic and cerebellar calcification with confirmed T2 flair MRI images confirming bilateral, asymmetrical white matter hyperintensities involving periventricular tracts. Diagnostic Formulation: 1. Fahr’s syndrome due to hypoparathyroidism, 2. Mood and psychotic disorder due to Fahr’s Syndrome, 3. Major neurocognitive disorder due to possible Fahr’s Syndrome with psychotic symptoms, 4. Epilepsy, 5. Subclinical hypothyroidism, 6. Bilateral eye cataracts. Parenteral calcium, magnesium, thiamine, folate and vitamin D oral supplements were prescribed. Olanzapine was titrated to 10mg, following a failed trial of risperidone. Lamotrigine was prescribed to augment the therapeutic sodium valproate. Upon discharge, her pharmacological treatment consisted of: 1) Lamotrigine 75mg per os (po) bi-daily (bd), 2) Epilim CR 300mg po bd, 3) Vitamin D supplementation, 4) Eltroxin 75ug po daily, 5) Olanzapine 15mg po nocte, 6) Titralac 2 tabs po ter die sumendum (tds), 7) Folate 5 mg po daily, 8) Thiamine 100mg po tds. A referral to ophthalmology was made regarding the cataract’s diagnosis. Conclusion: Radiological and biochemistry investigations should be motivated for in resource limited settings when assessing atypical psychosis. This case report highlighted neurobehavioral and neurocognitive symptoms may develop and persist in a patient with Fahr’s syndrome.